Examining the linkage between political skill, emotional labor strategies, and individual outcomes: Evidence from Chinese hotel industry - Muhammad Usman; Fan Luo; Muhammad Anwar-ul-Haq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
The purpose of this study is to examine the linkage between political skill, emotional labor strategies, and two individual level outcomes; emotional exhaustion and subjective career success in the context of Chinese hotel industry. Political skill is hypothesized to have negative impact on surface acting, conversely, it was hypothesized to have positive impact on deep acting. Similarly, political skill is proposed to positively predict subjective career success and negatively to emotional exhaustion. Interactive effect of political skill with subjective career success and emotional exhaustion as outcome with surface acting as antecedent was also proposed. The emotional labor strategies were also hypothesized with emotional exhaustion and subjective career success as outcome variables. The setting of the study were hotels operating in Wuhan, Peoples' Republic of China. Frontline hotel staff responded 212 questionnaires. Covariance based Structural Equations Modeling was used to conduct the factor analysis and test the hypothesis, AMOS V 20.0 was used for the purpose. Results show that political skill is a positive predictor of subjective career success, and a negative predictor emotional exhaustion. Emotional labor strategies were also related with emotional exhaustion and subjective career success as hypothesized. Political skill confirmed the hypothesized interactive effect with surface acting to predict emotional exhaustion and subjective career success. Lastly, the implications for theory, policy, practice and future research have been given
Keywords: 330; Political skill; deep acting; surface acting; subjective career success; emotional exhaustion; hotel industry; China